Metabolomic analysis of murine tissues infected with Brucella melitensis. - Bárbara Ponzilacqua-Silva; Alexis S Dadelahi; Charles R Moley; Mostafa F N Abushahba; Jerod A Skyberg (PLoS ONE)
Brucella is a gram negative, facultative intracellular bacterial pathogen that constitutes a substantial threat to human and animal health. Brucella can replicate in a variety of tissues and can induce immune responses that alter host metabolite availability. Here, mice were infected with B. melitensis and murine spleens, livers, and female reproductive tracts were analyzed by GC-MS to determine tissue-specific metabolic changes at one-, two- and four- weeks post infection. The most remarkable changes were observed at two-weeks post-infection when relative to uninfected tissues, 42 of 329 detected metabolites in reproductive tracts were significantly altered by Brucella infection, while in spleens and livers, 68/205 and 139/330 metabolites were significantly changed, respectively. Several of the altered metabolites in host tissues were linked to the GABA shunt and glutaminolysis. Treatment of macrophages with GABA did not alter control of B. melitensis infection, and deletion of the putative GABA transporter BMEI0265 did not alter B. melitensis virulence. While glutaminolysis inhibition did not affect control of B. melitensis in macrophages, glutaminolysis was required for macrophage IL-1β production in response to B. melitensis. In summary, these results indicate that Brucella infection alters host tissue metabolism and that these changes could have effects on inflammation and the outcome of infection.